1994
DOI: 10.1007/bf00588132
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiography in meningovascular syphilis

Abstract: Meningovascular neurosyphilis (MN) is an unusual cause of stroke in young adults. The clinical manifestations include prodromal symptoms weeks or months before definitive stroke. The diagnosis is based on clinical findings and examination of the serum and cerebrospinal fluid. We report a case of MN with basilar artery irregularities demonstrated by magnetic resonance angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 10 publications
3
11
0
5
Order By: Relevance
“…Additionally, mesial temporal lobe atrophy has been recognized as a particular feature of general paresis. 8 Russouw's study showed that lesions in the temporal lobes were related to lower scores on the MiniMental State Examination. 9 In our study, four patients had various degrees of cerebral atrophy or mesial temperal lobe atrophy.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, mesial temporal lobe atrophy has been recognized as a particular feature of general paresis. 8 Russouw's study showed that lesions in the temporal lobes were related to lower scores on the MiniMental State Examination. 9 In our study, four patients had various degrees of cerebral atrophy or mesial temperal lobe atrophy.…”
Section: Discussionmentioning
confidence: 98%
“…Los hallazgos imaginológicos (TM y RM) del encéfalo en pacientes con neurosífilis no son específicos y son diversos: atrofia cerebral (50 %), lesiones isquémicas (43 %) (como este paciente), lesiones en la sustancia blanca (50 %) y arteritis (29 %) (21,22). Los infartos se presentan con mayor frecuencia en lóbulos cerebrales, corona radiada, tallo cerebral, ganglios basales, cuerpo calloso y la circunvolución del cíngulo (23).…”
Section: Discussionunclassified
“…With regard to the CTor MRIfindings of meningovascular syphilis, Holland et al (3) presented multifocal infarctions correlated with varying degrees of narrowing and ectasia of the supratentorial cerebral artery. However, in a review of the current literature, limbic lesions have not been described in syphilitic meningovasculitis (1,3,4). On the other hand, in genera] paresis, cerebral cortical atrophy and white matter changes have been emphasized (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) or single-photon emission computed tomography (SPECT) of meningovascular neurosyphilis and general paresis have revealed multifocal lesions due to vasculitis, cerebral cortical atrophy, white matter changes, and the reduction of cerebral blood flow (3,4). Wereport a case of neurosyphilis in a non-immunocompromisedpatient showing transient global amnesia (TGA)-like attacks, and MRI abnormalities mainly in the bilateral medial temporal lobes.…”
Section: Introductionmentioning
confidence: 99%